Women Political Participation -Opportunities And Challenges: A Case study of District Kulgam of Jammu and Kashmir State, India - Ahmad Wagay, Muzamil; Al Abdullah, Sareem (IJRDO - Journal of Social Science and Humanities Research, 2016)
This study was undertaken to understand the socio economic, political and educational background of the women representatives in the district Kulgam of Jammu and Kashmir, India. To find out the factors that hinder process of political participation of women of the area under study.To explore the awareness, interests and involvement of women elected in Halqa panchayat.The study explores the involvement of elected women members in decision-making and attempts at understanding the change in attitudes and role perception of women representatives after being elected.Kulgam district comprises of 5 blocks including Devsar, D.H Pora, Kulgam, Pahloo, and Quimoh (main block). There are total of 76 females Panchs in Block Devsar out of which 8 were taken for the study. From D.H. Pora out of 102 female Panchs 10 were taken. From Kulgam out of total 57 Panchs 6 were selected. From block Pahloo out of 32 Panchs 3 were taken and from block Quimoh main block out of total 37 female Panchs 3 were selected. So a sample of 10 % from each block was randomly selected.Tools used were structured questionnaire, Personal observationand Collection of data from official sources (Rural Development Department, Kulgam).The study findings affirm the variations in the political profile of the female elected Panchs. Majority of them were not having any political affiliations but the pressure from family especially from husbands paved their way into the local bodies.It was observed from the study that a major section of elected women representatives were illiterate.The study recorded that the decision making of women is low.It was observed that the major obstacle for female Panchs was male dominance.The study confirms the value of gender quotas as an important tool for moving us toward our goal of gender responsive governance, insofar as the mere presence of women can transform patriarchal frameworks